Feminist view in Emily Dickinson's selected poems - Arsyad, Nisrina Muthi'ah; Salsabillah, Tiara Auliya (Journal of Language and Pragmatics Studies, 2024)
The study focuses on Emily Dickinson’s poems that express feminist views and societal expectations toward women. The selected poems, “They Shut Me Up in Prose –” and "She Rose to His Requirement – drop", explore how Dickinson’s poems connect to feminism and literature. In order to gain a deeper understanding of how literature can serve as a medium for social criticism and individual expression, the researchers used the qualitative archival and documents technique in this study. The result of this study shows feminist literary criticism and ecofeminism that Emily Dickinson used in her poetry. The researchers also find historical context and intersectionality in Dickinson’s poems.